Effect of ply-drop on fatigue life of a carbon fiber composite under a fighter aircraft spectrum load sequence. (1st February 2016) - Thawre, Manjusha M.; Verma, K.K.; Jagannathan, N.; Peshwe, D.R.; Paretkar, R.K.; Manjunatha, C.M.
Abstract: Carbon fiber composite laminate containing symmetric internal ply-drop simulating thickness variation was fabricated and tested to determine fatigue life under a standard mini-FALSTAFF spectrum load sequence. The fatigue life of ply-drop composite was significantly lower than that of plain composite due mainly to initiation and growth of delamination near the ply-drop location. The spectrum fatigue life was also predicted by empirical method. For this purpose, static and constant amplitude fatigue data was generated to construct constant life diagrams (CLDs). The spectrum fatigue life predicted using CLDs was in good agreement with experimental results for both plain and ply-drop composites.